Efecto en la variación de temperatura en la incubación de huevos fértiles COBB-500 - Zambrano Loor, Robert Ignacio (2022)
1552 Cobb 500 eggs were incubated to evaluate the effect of different temperatures on incubation parameters. The research was inductive, supported by observation and recording techniques, it was established with four treatments T1 37.2 °C; T2 37.5°C; T3 37.8 °C and T4 38.00 °C, distributed in a completely random design. The variables were measured: eggs eliminated in candling (%), embryonic mortality (%), weight loss in incubation (%), first-class chicks (%), hatchability (%), bb chicken weight, chick weight yield (%). The percentage of eggs extracted by candling did not present significant differences (p > 0.05), early and intermediate embryonic mortality showed significant differences (p < 0.05) between treatments, while there were no differences in late embryonic death, the percentage of weight loss in incubation showed significant differences (p < 0.05), where T4 presented the greatest weight loss (13.67%) compared to T1, which obtained 9.29%. No significant differences (p > 0.05) were found for first-class chicks and hatchability. The percentage of weight yield of the chick in relation to the initial weight of the egg showed significant differences (p < 0.05), since T1 is the treatment with the best yield with 74.03% compared to T4, which reached 69.41%. It is concluded that the temperature variation in incubation influences certain incubation parameters of Cobb 500 eggs, but there is no effect on the production of first-class chicks and the percentage of hatchability.